INNOVATIVE ACTIVITY OF ENTERPRISES OF THE AGRICULTURAL SECTOR OF UKRAINE: ASSESSMENT OF THE SITUATION AND MARKETING FACTORS OF DEVELOPMENT - ALSHABAN, ALAA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the study of the theoretical foundations of innovative development of agricultural enterprises. The conditions of innovative development of enterprises of the agricultural sector of Ukraine are studied. The necessity of complex application of innovative tools by enterprises of the agricultural sector is proved: the latest equipment, resource-saving technologies, production structure, qualified personnel, marketing innovations, managerial and organizational innovations. It is proved that the innovation process should consider the stages of the life cycle of agricultural technology: from the idea to its development and practical implementation in the production of innovative agricultural technology, as well as its market implementation, including marketing and purchasing products by end users. The contradiction between the use of innovations in the agricultural sector and the possible deterioration of the ecological state of the environment was revealed. An assessment of the innovative activity of enterprises in the agricultural sector, as well as proposed measures to improve it. The influence of the size of an agricultural enterprise on the volume and structure of capital investments is considered. Analysis of statistical data shows an increase in the amount of capital investment in the agricultural sector of Ukraine in 2 times from 2015 to 2019. At the same time capital investment in intangible assets has increased significantly - almost 8 times, including investments in intellectual property and marketing. The analysis shows that the large enterprises of the agricultural sector have greater opportunities to implement organizational and marketing innovations. Indicators of acquisition and use of agricultural machinery, import of breeding animals, structure of species composition of varietal resources are analyzed. The data confirm the increase in the number of purchased agricultural machinery in enterprises of the agricultural sector, especially tillage and sowing, which indicates the strengthening of innovation in crop production. Features and obstacles to the use of innovative processes of agricultural enterprises have been clarified.